Indicator Supraparticles for Smart Gasochromic Sensor Surfaces Reacting Ultrafast and Highly Sensitive - Wintzheimer, Susanne; Oppmann, Maximilian; Dold, Martin; Pannek, Carolin; Bauersfeld, Marie-Luise; Henfling, Michael; Trupp, Sabine; Schug, Benedikt; Mandel, Karl (Particle & Particle Systems Characterization, 2019)
The detection of toxic gases, such as NH3 and CO, in the environment is of high interest in chemical, electronic, and automotive industry as even small amounts can display a health risk for workers. Sensors for the real-time monitoring of these gases should be simple, robust, reversible, highly sensitive, inexpensive and show a fast response. The indicator supraparticles presented herein can fulfill all of these requirements. They consist of silica nanoparticles, which are assembled to supraparticles upon spray-drying. Sensing molecules such as Reichardt's dye and a binuclear rhodium complex are loaded onto the microparticles to target NH3 and CO detection, respectively. The spray-drying technique affords high flexibility in primary nanoparticle size selection and thus, easy adjustment of the porosity and specific surface area of the obtained micrometer-sized supraparticles. This ultimately enables the fine-tuning of the sensor sensitivity and response. For the application of the indicator supraparticles in a gas detection device, they can be immobilized on a coating. Due to their microscale size, they are large enough to poke out of thin coating layers, thus guaranteeing their gas accessibility, while being small enough to be applicable to flexible substrates.
CRIS-Team Scopus Importer:2020-04-02
Keywords: CO sensing; NH; sensor supports; silica supraparticles; smart surfaces